Athletica Pro Design: Perangkat Portabel untuk Pemantauan Denyut Jantung, Saturasi Oksigen, dan Pengatur Waktu dalam Aktivitas Olahraga - Gema Kharismajati; Daviq Nariel Islamy; Ivan Dwi Setyawan; Hadiono Hadiono; Andryas Yuniarto (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. Athletica Pro is an innovative portable device designed to provide a comprehensive solution for health monitoring during sports activities. Materials and methods. This device integrates advanced electronic components, including the Arduino Nano, MAX30102 sensor, OLED SSD1306 display, RTC DS3231 module, and LiPo battery, ensuring accurate and reliable monitoring of heart rate, oxygen saturation, and timer functions. Result. The results of the effectiveness test show that Athletica Pro delivers highly precise data under various sports conditions, making it an essential tool for athletes and coaches who require real-time and dependable health monitoring. With cutting-edge technology and an efficient design, this device not only aids in maintaining athletes' health but also can help improve athlete performance through better heart rate monitoring Conclusion. These findings suggest Athletica Pro is a viable alternative to commercial health monitors for athletes.